2023
DOI: 10.1007/s43615-023-00251-8
|View full text |Cite
|
Sign up to set email alerts
|

ESGs and Customer Choice: Some Empirical Evidence

Abstract: The goal of this paper is to determine whether a company’s performance on environmental, social, and governance (ESG) indicators influences customer choice, and if so, which ones are the most important, as well as whether the COVID-19 pandemic had an effect on changing this hierarchy. Additionally, it intends to investigate the influence of regional and demographic factors on its formation. To achieve this goal, primary data were gathered in Greece via a questionnaire survey. According to the findings, a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[31,32]). In the context of sustainability, companies' performance on environmental, social, and governance (ESG) issues affects consumer choice, with an emphasis on environmental and social indicators [33]. According to Laukkanen and Tura, customer-perceived value assists the design of dynamic sustainable value propositions to respond to market changes and builds an understanding of the expected sustainability impacts [24].…”
Section: Perceived Value On Sustainable Business Modelsmentioning
confidence: 99%
“…[31,32]). In the context of sustainability, companies' performance on environmental, social, and governance (ESG) issues affects consumer choice, with an emphasis on environmental and social indicators [33]. According to Laukkanen and Tura, customer-perceived value assists the design of dynamic sustainable value propositions to respond to market changes and builds an understanding of the expected sustainability impacts [24].…”
Section: Perceived Value On Sustainable Business Modelsmentioning
confidence: 99%
“…It can be asserted that because of the volatile economic environment and the increasing interest of investors, consumers [25] employees, and governments due to socio-economic and environment issues, as well as the increasing legal action taken against a corporate entity or its shareholders, managers wish to focus on reputation-building, their fiduciary responsibilities, and their moral responsibilities [2]. Some studies [26,27] have shown a favorable assessment when entities disclose their ESG index.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green supply chain management (GSCM) integrates environmental thinking into supply chain management, creating a sustainable supply chain [ 5 ]. As noted in the relevant literature (see, e.g., [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]) companies are under immense pressure to adopt GSCM practices that are driven towards the environment by a combination of external factors (government rules and legislation; environmental concerns and regulation; social and environmental responsibility; customer awareness, pressure, and support; supplier pressure and willingness; global climate pressure) and internal factors (green image; global marketing; competitiveness; economic beliefs or cost reduction benefits; investor and shareholder pressure; employee motivation; health and safety issues; waste management issues) towards meeting SDGs, as they directly affect customer choice [ 15 ]. Furthermore, many studies are currently focusing on discussing the implementation of GSCM in different sectors of the economy and/or specific countries (see, e.g., [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]).…”
Section: Introductionmentioning
confidence: 99%